PENERAPAN MODEL NUMBER HEAD TOGETHER DENGAN MEDIA FLASHCARD DALAM PENINGKATAN PEMBELAJARAN MATEMATIKA SISWA KELAS IV SD NEGERI 3 DOROWATI TAHUN AJARAN 2014/ 2015 - Pratiwi, Ulva (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: The Use of Number Head Together  Model  Through Flashcard Media in Improving Mathematics at the Fourth Grade Students of SD Negeri 3 Dorowati in the Academic Year of 2014/2015.  The objectives of this research are:  (1) to describe the implementation of number head together  model through flashcard media (2) to describe the improvement of Mathematics learning (3) to identify problems and solutions in the implementation of number head together  model  through flashcard media. This research is collaborative Classroom Action Research (CAR) conducted in three cycles. Subject in this research were 25 students of the Fourth Grade Students of SD Negeri 3 Dorowati. Conclusion of this research is the implementation of number head together  model  through flashcard media implemented with appropriate steps can improve Mathematics learning at the fourth grade students of SD negeri 3 dorowati in the academic year of 2014/2015. Keywords: number head together, flashcard, Mathematics Abstrak: Penggunaan Model Number Head Together dengan Media Flashcard Pembelajaran Matematika Siswa Kelas IV SD Negeri 3 Dorowati Tahun Ajaran 2014/2015. Tujuan penelitian ini adalah  (1) mendeskripsikan penerapan model number head together dengan media flashcard (2) mendiskripsikan peningkatan pembelajaran Matematika (3) mengidentifikasi kendala dan solusinya. Penelitian ini merupakan Penelitian Tindakan Kelas (PTK) kolaboratif yang dilaksanakan selama 3 siklus. Subjek penelitian ini adalah siswa kelas V SD Negeri 3 Dorowati yang berjumlah 25 siswa. Simpulan penelitian penerapan model number head together dengan media flashcard yang dilaksanakan dengan langkah-langkah yang tepat dapat meningkatkan pembelajaran Matematika siswa kelas IV SD Negeri 3 Dorowati Tahun Ajaran 2014/2015. Kata Kunci: number head together,  flashcard, Matematika